Cycloaddition Reactions of N-Benzotriazolylketene as a Heteroarylketene: A Practical Approach to the Synthesis of Novel Azetidinones - Zigheimat, Fatemeh; Islami, Mohammad Reza; Nourmohammadian, Farahnaz (Synlett, 2014)
A series of novel functionalized azetidinones containing the benzotriazole moiety were synthesized stereoselectively by a reaction of benzotriazolylacetic acid, aromatic amines, and Mukaiyama’s reagent in the presence of triethylamine in dichloromethane at ambient temperature. This transformation generates a four-membered lactam and presumably proceeds via in situ generation of benzotriazolylketene as a heteroarylketene. In contrast to the products obtained from the reaction of pyrrolylketene with imines in which cis-azetidinones were formed as major products, the generated benzotriazolylyketene reacted with imines forming the trans-lactams as major products.
Keywords: ketenes; Schiff bases; N-benzotriazolylketene; [2π+2π] cycloaddition; azetidinones